EXPLORING EFFECTIVE PEDAGOGICAL APPROACHES TO PHYSICAL EDUCATION DURING ADOLESCENCE - Z.R. Dzhomaladinova, (World Scientific Research Journal, 2025)
Abstract: Adolescence is a pivotal period for instilling lifelong attitudes and behaviors towards physical activity. This review paper seeks to examine and synthesize current pedagogical approaches to physical education (PE) specifically tailored to meet the developmental needs of adolescents. The paper discusses the importance of a multifaceted approach that combines skill development, motivation enhancement, and socio-emotional support to address the unique physical and psychological changes that occur during this life stage. By analyzing empirical studies, educational frameworks, and progressive teaching methodologies, this article aims to offer insight into creating PE programs that foster a positive attitude towards physical health, improve physical literacy, and enhance overall well-being among adolescents.